Health during industrialization: evidence from the 19th century Pennsylvania state prison system - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2007)
The use of height data to measure living standards is now a well-established method in economic history. Moreover, a number of core findings in this literature are widely agreed upon. There are still some populations, places, and times, however, for which anthropometric evidence remains thin. One example is African-Americans in the US Northeast and Middle Atlantic states during the 1800s. Here, a new data is used from the Pennsylvania state prison to track black and white male heights incarcerated between 1829 to 1909. Throughout the century, and controlling for a number of characteristics, Pennsylvania black men in were shorter than white men. The well-known mid-century height decline is confirmed among white men, however, extended to blacks as well.
Keywords: N31; J15; J70; I12; I31; 330